EXPERIMENTAL STUDY OF LITHIUM DENDRITE SUPPRESSION FOR LITHIUM-ION BATTERIES - (:unkn) unknown (My University, 2024)
Lithium metal is considered one of the most promising anodes in next-generation lithium-ion batteries (LIBs). However, it faces several challenges in cycling performance due to lithium dendrites, dead lithium, corrosion, and volume expansion by lithium. On the basis of electrochemical principle, failure mechanism, and recent advancements in LIBs, we optimized the amorphous GeOx layer that is bonded on Ti3C2 MXenes layers on lithium metal. The designed composite coating was achieved by applying optimal ratio of GeO2 and monolayer MXene with a selected reduction time. When paired with high capacity LiNi0.8Co0.15Al0.05O2 (NCA) as the cathode material, the battery displayed higher capacity retention compared with pure lithium metal. The improved performance and capacity retention observed in this study highlight the potential of the developed composite coating in addressing the challenges associated with lithium metal anodes. This research contributes to the ongoing efforts in advancing the stability and performance of lithium metal anodes. Further investigations on the electrochemical properties and long-term stability of the optimized composite coating can provide valuable insights for the future design.